(untitled) (Research, Society and Development, 2023)
Histology is the science that studies the microscopic structures of human organs and tissues. For this study to happen efficiently, visualizing the cell and tissue structures, microscopy techniques are used, which may be conventional and/or virtual. Therefore, the objective of this study is to identify in the literature the use of virtual microscopy compared to conventional microscopy in the teaching of histology. This is a narrative literature review, of an explanatory nature, carried out according to a bibliographic survey in the following electronic databases: PubMed, SciELO, LILACS, BVS and Scholar Google. As search strategy, the following Health Science Descriptors (DeCS) were used: "dentistry", "virtual microscopy", "conventional microscopy" and "learning". Twenty-two references were selected for the study, delimited from 2009 to 2022, in Portuguese and English. Based on the literature studied, it became evident that virtual microscopy has several advantages over virtual microscopy, such as ease of interaction between students and teacher, time optimization and the opportunity to review histological slides outside a conventional laboratory. Conventional microscopy enables the student to actively engage through interaction with a physical microscope, and increases the use and longevity of the method. Virtual microscopy has several advantages over conventional microscopy, but both acts together, complementing each other. Thus, it is essential that during histological teaching the two methods are used in order to enhance the learning process of health students.